Medical Tourism in the Philippines: Market Profile, Benchmarking Exercise, and S.W.O.T. Analysis - Oscar F. Picazo (Philippine Institute for Development Studies (PIDS), 2013)
This report reviews the medical tourism industry in the Philippines. It discusses the global market for medical tourism, analyzes the demand and supply aspects of the local industry, and identifies its drivers of growth. It performs an industry benchmarking exercise by looking at benchmarks associated with strategy setting, organization and management, service quality, care, travel and accommodation, and financing. It also conducts an analysis of the strengths, weaknesses, opportunities, and threats of the industry.
Keywords: 330; Philippines; medical tourism; industry benchmarks; market profile; demand for medical tourists; supply of services and facilities for medical tourism